2021
DOI: 10.1002/lary.29817
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Movement and Silent Aspiration After Congenital Heart Surgery

Abstract: Objectives/Hypothesis: Infants who undergo congenital heart surgery are at risk of developing vocal fold motion impairment (VFMI) and swallowing difficulties. This study aims to describe the dysphagia in this population and explore the associations between surgical complexity and vocal fold mobility with dysphagia and airway protection.Study Design: Retrospective chart review. Methods: This is a retrospective chart review of infants (age <12 months) who underwent congenital heart surgery between 7/2008 and 1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…14 However, some studies did not observe a correlation between the categories on RACHS/STAT and the oral feeding outcomes in newborns and infants. 14,28 Variability of postsurgery complications such as vocal fold paralysis and vocal fold mobility impairment secondary to recurrent laryngeal nerve injury may be contributing this discrepancy. 25,28,29,39,40 A study that assessed the swallowing dysfunction using Modified…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, some studies did not observe a correlation between the categories on RACHS/STAT and the oral feeding outcomes in newborns and infants. 14,28 Variability of postsurgery complications such as vocal fold paralysis and vocal fold mobility impairment secondary to recurrent laryngeal nerve injury may be contributing this discrepancy. 25,28,29,39,40 A study that assessed the swallowing dysfunction using Modified…”
Section: Discussionmentioning
confidence: 99%
“…14,28 Variability of postsurgery complications such as vocal fold paralysis and vocal fold mobility impairment secondary to recurrent laryngeal nerve injury may be contributing this discrepancy. 25,28,29,39,40 A study that assessed the swallowing dysfunction using Modified…”
Section: Discussionmentioning
confidence: 99%
“…7,15 Several studies have demonstrated that VFMI is a risk factor for silent aspiration after congenital surgery and an independent risk factor for interstage death after the Norwood procedure, highlighting the importance of surveillance and management in this population. 1,7,16,17 Postoperative vocal fold evaluation can be critical in diagnosing asymptomatic VFI, and detecting silent aspiration earlier, as well as optimizing postoperative feeding management strategies to prevent adverse sequelae. Routine adoption of LUS as a primary modality for assessment of vocal fold motion has gained traction in the pediatric neonatal population.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating patients with vocal fold movement impairment, it is important to determine if this was acquired or congenital and assess the probability of return of vocal fold function and resolution of dysphagia. For instance, in the cardiac population, there are data that demonstrate that resolution of swallowing difficulties may occur independently of return of vocal fold function [52,53 ▪ ]. In addition to speech therapy, temporary or permanent interventions can be considered.…”
Section: Surgical and Medical Managementmentioning
confidence: 99%